2018
DOI: 10.1088/2058-6272/aa89e1
|View full text |Cite
|
Sign up to set email alerts
|

Study of electron-extraction characteristics of an inductively coupled radio-frequency plasma neutralizer

Abstract: Inductively coupled radio-frequency (RF) plasma neutralizer (RPN) is an insert-free device that can be employed as an electron source in electric propulsion applications. Electron-extraction characteristics of the RPN are related to the bulk plasma parameters and the device's geometry. Therefore, the effects of different electron-extraction apertures and operational parameters upon the electron-extraction characteristics are investigated according to the global nonambipolar flow and sheath model. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Filament cathodes consume 0.1-100 W mA −1 in heater power, and lifetimes are severely limited by thermal cycling [8]. Plasma cathodes are insert-free devices that can be employed as electron sources in electric propulsion applications [9,10]. Plasma cathodes also reduce the specific impulse of the propulsion system due to use of propellant to sustain plasma.…”
Section: Neutralization Control Strategymentioning
confidence: 99%
“…Filament cathodes consume 0.1-100 W mA −1 in heater power, and lifetimes are severely limited by thermal cycling [8]. Plasma cathodes are insert-free devices that can be employed as electron sources in electric propulsion applications [9,10]. Plasma cathodes also reduce the specific impulse of the propulsion system due to use of propellant to sustain plasma.…”
Section: Neutralization Control Strategymentioning
confidence: 99%
“…其中, 惯性传感器是无拖曳控制系统 的传感机构, 为了达到引力波探测的要求, 其加速度读出噪 声应低于 3×10 −15 m s − 2 Hz − 1/2 [60,61] . 微推进器可有多重选择, 比如 FEEP [62] , RIT [63,64] , 胶体 [65] , 冷气 [66] 以及霍尔 [67] 等, 要 求微推进器分辨率≤0.1 μN, 噪声水平≤0.1 μN/Hz 1/2 [68] . [71] , 帮助理解和 解决上述由复杂系统引出的科学问题.…”
Section: 激光干涉测距系统unclassified
“…Jahanbakhsh et al discussed the relationship between the electron extraction capacity and the gas flow rate, the size of the extraction aperture, and the absorbed RF power [10,21]. According to another theory, the anode spot has an impact on the electron extraction property [22,23]. A comparison of numerical and experimental results showed that the effects of target voltage, aperture diameter, gas flow rate and RF power were consistent [24].…”
Section: Introductionmentioning
confidence: 99%